Pengaruh Investment Opportunity Set, Dividend Payout Ratio dan Mekanisme Corporate Governance Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Syafda, Nur Insyiroh; Puspaningsih, Abriyani (Unisia, 2012)
This research was aimed to expose the effect of investment Opportunity Set, Dividend Payout Ratio and Corporate Governance Mechanism to the Company's Value. In this research, company's value was measured by Tobin's Q. Corporate Governance Mechanism were measured by audit committee, independent directors, institutional ownership and managerial ownership. Sampels in this research were 14 manufacturing company that listed at Indonesian Stock Exchange 2008-2010. Data processing in this research was supported by statistic program (SPSS). The data analysis was carried on by regression analysis. The result from the analysis showed that investment Opportunity Set, independent directors, institutional ownership and managerial ownership were affected to company's value. Dividend Payout Ratio and audit committee were not affected to company's value. Keywords: Corporate Governance, Dividend Payout Ratio, Investment Opportunity Set, Tobin's Q.